Infant feeding and atopy. Issue 9 (September 1987) - Midwinter, R E; Morris, A F; Colley, J R
Abstract : Parents of 457 5 year olds from a previous study of infant feeding and eczema in the first year of life were questioned about subsequent atopy. No association was found with early breast or bottle feeding. Family history was important. Parental recall of first year eczema was often inaccurate.